PENINGKATAN KETERAMPILAN BERBICARA PESERTA DIDIK MENGGUNAKAN MODEL PAIRED STORYTELLING SISWA KELAS V SDN 15 AMPANG GADANG KABUPATEN AGAM - Nadiya Ulfah; Elfia Sukma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the lack of optimal speaking skills in learning which has an impact on the low speaking ability of grade V students of SDN 15 Ampang Gadang, Agam Regency. This study aims to determine the application of the Paired Storytelling model to improve the speaking skills of class V students of SDN 15 Ampang Gadang, Agam Regency. This type of research is classroom action research using qualitative and quantitative approaches. This research was carried out in two cycles. Each cycle has four stages, namely planning, implementation, observation, and reflection. The subjects of this study are 18 teachers and students of class V, consisting of 7 male students and 11 female students. The results of the research of the first cycle of the teaching module obtained a percentage of 87.5% with good qualifications (B), increased in the second cycle to 97.5% with very good qualifications (A). Teacher activity in the first cycle obtained a percentage of 85% with good qualifications (B), increased in the second cycle to 95% with very good qualifications (A). Student activities in the first cycle obtained a percentage of 85% with good qualifications (C), increasing in the second cycle to 95%. The learning outcomes of students in the first cycle of knowledge assessment were obtained on average 66.67 with poor qualifications (D), increased in cycle II to 85.6 with good qualifications (B). The results of the first cycle of skill assessment were obtained on average 72.68 with sufficient qualifications (C), increased in the second cycle to 85.6 with good qualifications (B). Based on these results, it can be concluded that the Paired Storytelling model can improve the speaking skills of grade V elementary school students.